ANALYSIS OF THE MORPHOLOGICAL AND BIOLOGICAL FEATURES OF TOMATO (SOLANUM LYCOPERSICUM) AND ITS ROLE IN AGRICULTURE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Tomato (Solanum lycopersicum) is one of the most important agricultural crops globally, cultivated worldwide. The fruit is characterized by a high content of biologically active compounds, such as lycopene, β-carotene, vitamin C, and others. This article discusses the botanical characteristics of tomato, its morphological and biological features, and evaluates its role in agriculture.